Monitoring Fuel Oil Based Radio Frequency Identification (RFID) Client - Dezar Septiantono; Zulfatman Zulfatman; Budhi Priyanto (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Motorcycles are a means of transportation which plays an important role in people's lives. One of the existing problems on the motorcycle is the indicator system or often called by speedometer, an indicator system showing the value of the volume of fuel oil. In fact, the sensor unit used by the indicator is not a volume sensor but the surface of the fuel sensor in the form of mechanical potentiometers. This equipment irregularly measures oil tank so that the mathematical approach to formulate the relationship between surface height and gasoline volume will be difficult. Therefore, to interpret the data manipulation done by comparison method is the method of comparison experiment and calculation. This method is applied in this research due its more superior accuracy and efficiency. This research designs hardware for monitoring fuel oil based on Radio Frequency Identification (RFID) using AT mega 328 as main controller and LCD to display driver’s identity sent by General Packet Radio Service (GPRS). The sensor used is a buoy sensor, measuring the fuel volume between 0.20 liters to 9.55 liters. It is known that the comparative method has an average rate of 16.1%, in measuring the fuel volume between 0.20 liters to 3.68 liters. It is known that the comparative method has an average rate of 17.9%. On measuring the fuel volume between 0.20 liters to 3.43 liters, the comparative method having an average rate of 7.2% is employed. Based on the test results, the best comparison method in comparison with the interpolation method with the average rate of smallest 7.2% is determined.